Konstitusionalitas Kewenangan Badan Usaha Milik Daerah dalam Pengelolaan Energi Baru dan Terbarukan - Nivia, Nivia; Ruhpinesthi, Garuda Era; Ismaya , Alfatania Sekar; Wicaksana, Aditya Sewanggara Amatyawangsa (Jurnal Konstitusi, 2024)
This research focuses on the constitutionality of the Regional-Owned Enterprises authority in the management of New and Renewable Energy. There are two research objectives to be obtained. First, the classification of EBT in the major production branches and the dominance over people’s lives refers to the dynamics of laws and decisions of the Constitutional Court. Second, the determination of BUMD's authority over the management of EBT refers to the state's control rights according to MK. This research is normative legal research based on secondary data. This research showed two conclusions. First, the classification of EBT includes nuclear, coal methane gas, liquefied and gasified coal, geothermal, and water flows and waterfalls. Second, the position of BUMD is classified into two models; (1) BUMN is prioritized over BUMD; and (2) BUMD is equivalent to BUMN. However, for SDA which are not included in this qualification, the position of these entities are equal.